Optimization of Filtered Rayleigh Scattering for the Measurement of Pressure and Temperature. Issue 8 (11th June 2022) - Feng, David; Goldberg, Benjamin M.; Shneider, Mikhail N.; Miles, Richard B.
ABSTRACT: The stand-off measurements of temperature and pressure are important for a variety of physical and engineering processes. Filtered Rayleigh scattering (FRS) configurations that enhance and suppress sensitivity to temperature are modeled and demonstrated using premixed, atmospheric methane-air Hencken burner generating temperatures up to 2100 K. For a characteristic flame gas mixture, modeling of the FRS signal using a molecular iodine filter shows that conditions exist for which the signal has a greater dynamic range or does not change significantly with respect to high gas temperatures. Laser Rayleigh scattering (LRS) measurements coupled with nonadiabatic flame simulations validate the temperatures, while FRS measurements are compared with the model predictions for different observation angles and iodine cell conditions. Results are discussed in the context of making direct measurements of gas pressure at high temperatures and within turbulent flames.